2012
DOI: 10.1177/0146167211427309
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Social Support Provision

Abstract: The present research examined cultural differences in the type and frequency of support provided as well as the motivations underlying these behaviors. Study 1, an open-ended survey, asked participants about their social interactions in the past 24 hours and found that European Americans reported providing emotion-focused support more frequently than problem-focused support, whereas Japanese exhibited the opposite pattern. Study 2, a closed-ended questionnaire study, found that, in response to the close other'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(158 citation statements)
references
References 33 publications
10
144
4
Order By: Relevance
“…People from individualistic cultures, such as the United States, tend to prefer coping strategies that are framed in terms of their own thoughts and feelings (e.g., Morling, Kitayama, & Miyamoto, 2003), and are more likely than people from collectivistic cultures to seek (Kim, Sherman, Ko, & Taylor, 2006; Mortenson, Burleson, Feng, & Liu, 2005;Shams, 2001;Taylor et al, 2004; for reviews, see Feng & Burleson, 2006;Kim, Sherman, & Taylor, 2008) and value emotional support (Burleson & Mortenson, 2003) or emotional expression (Butler, Lee, & Gross, 2007, 2009. Therefore, the following hypothesis was proposed based on the above reasoning and review of relevant literature:Hypothesis 4 (H4): American participants will respond to advice offered in conjunction with emotional support more positively than Chinese participants.There is research evidence showing that in collectivistic cultures, offering problemfocused support such as advice is a culturally appropriate way to respond to others' stress (Chen et al, 2012;Chentsova-Dutton & Vaughn, 2012). Relatedly, accommodating to others' influence attempts, especially when the influencer is believed to have an other-serving motive (e.g., helping the target solve a problem), is normative in collectivist cultures (Savani, Morris, Naidu, Kumar, & Berlia, 2011).…”
mentioning
confidence: 99%
“…People from individualistic cultures, such as the United States, tend to prefer coping strategies that are framed in terms of their own thoughts and feelings (e.g., Morling, Kitayama, & Miyamoto, 2003), and are more likely than people from collectivistic cultures to seek (Kim, Sherman, Ko, & Taylor, 2006; Mortenson, Burleson, Feng, & Liu, 2005;Shams, 2001;Taylor et al, 2004; for reviews, see Feng & Burleson, 2006;Kim, Sherman, & Taylor, 2008) and value emotional support (Burleson & Mortenson, 2003) or emotional expression (Butler, Lee, & Gross, 2007, 2009. Therefore, the following hypothesis was proposed based on the above reasoning and review of relevant literature:Hypothesis 4 (H4): American participants will respond to advice offered in conjunction with emotional support more positively than Chinese participants.There is research evidence showing that in collectivistic cultures, offering problemfocused support such as advice is a culturally appropriate way to respond to others' stress (Chen et al, 2012;Chentsova-Dutton & Vaughn, 2012). Relatedly, accommodating to others' influence attempts, especially when the influencer is believed to have an other-serving motive (e.g., helping the target solve a problem), is normative in collectivist cultures (Savani, Morris, Naidu, Kumar, & Berlia, 2011).…”
mentioning
confidence: 99%
“…Chen and her colleagues showed that Japanese participants appeared to be more eager to provide support in order to achieve the goal of closeness and increased the support recipient’s self esteem more than European Americans [53]. It is likely that seeking instrumental support is not only a culturally acceptable type of support, but also a way for Asian/Chinese immigrants who were less acculturated to utilize this method to stay close with their support recipient.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because scores on personality-related scales (such as caregiving) fluctuate somewhat across cultures (Chen, Kim, Mojaverian, & Morling, 2012), we recommend replicating our study in different cultures in order to obtain a more comprehensive view of how caregiving relates to life satisfaction and physical health.…”
Section: Study Limitations and Directions For Future Researchmentioning
confidence: 99%